THE LEGAL CONSEQUENCES REGARDING THE EXECUTION OF JOINT PROPERTY LAND OBTAINED DUE TRANSNATIONAL MARRIAGE IN INDONESIAN POSITIVE LAW - Nurhayati, Yati; Ifrani, Ifrani (Lambung Mangkurat Law Journal, 2018)
he arising issues of transnational marriage in Indonesia, Several problems they will face, among others will be concerning the children’s nationality because they are subject to different laws, as well as problems with their properties that were obtained during marriage, that is frequently related to the land ownership of Indonesian Citizen. Especially the status of land property right owned by Indonesian citizens that was obtained due the transnational marriage according to Indonesian positive law and the execution of the joint property separation,in the form of land. The research method that is used is a normative juridical approach which analyzed based on the jurisprudence. Based on Indonesian positive law, the citizen who in the transnational marriage without prenuptial agreement, the rights status of his/her land in the form of property acquired jointly be equalized to his/her partner is only the rights to use. The partition of land property acquired jointly when divorce occurs in a transnational marriage beyond the specified period time by the Indonesian Positive Law is not applicable based on article 21 paragraph (3) of UUPA.